Evaluation of the development of Fafia - Pfaffia glomerata (Spreng.) Pedersen - Ming, Lin Chau [UNESP]; Júnior, C. C. [UNESP] (My University, 2004)
The aim of this experiment is to evaluate the development in height of the plants of four accessions (2 from Parana - accession 1 and 2, one from São Paulo - accession 3, and one from Mato Grosso do Sul State- accession 4). The experimental design was made of randomized blocks, with four treatments (accessions) and four replications. In each plot were planted 24 seedlings. Five evaluations of the height were accomplished, with an interval of two months, starting from the second month after the planting of the seedlings. The results show a significant difference between accession 4 and other three accessions in first evaluation (141.42 % higher than accession 2, the lowest of three and 44.16 % higher than accession 3, the highest of three), demonstrating a higher vigour of this accession on initial stage of its development. In the second and third evaluation, all accessions have no statistical difference, demonstrating a similar level of development at intermedial stages of development. At 5 th evaluation, all accessions have almost the same result, with no statistical difference among them. This is a clear result of similar level of development of this species in these accessions, representing a stabilization of their height development at the end of first year. We concluded that fáfia possesses a strong initial growth, with visible difference among the accessions in the first months. From the eight month on, we observed a slight decrease in the height. This suggests the end of annual cycle.
Keywords: Height development; Medicinal plant